Pengaruh Pemberian Sensori Integrasi Terhadap Perubahan Motorik Kasar Anak Pada Anak Hiperaktif Di Klinik Tumbuh Kembang Anak Yamet Cabang Surabaya Timur - Jamilatus Sholeha; Angria Pradita; Sartoyo Sartoyo; Nurul Halimah (Jurnal Keperawatan Muhammadiyah, 2023)
Objective:  Hyperactivity is a condition that causes children to be less focused, easily distracted by the environment, impulsivity and over activity. At toddler age it is usually followed by delays in gross motor development due to lack of motion control and causing lots of unnecessary movements. Sensory Integration is a method  of processing information obtained through some human senses in auditory, visual, tactile, as well as vestibular and proprioceptive forms that are transmitted to the brain.. Methods:  This research has 15 respondents using purposive sampling. The research design uses a quas type with a one group pretest and posttest approach.Results:  The result in this study, there was  an effect of sensory integration on gross motor changes at the yamet child development center east surabaya branch with a p-value = 0.001 (p<0.05).Conclusion:   1.  Most respondents scored FEAS value before the provision of sensory integration, namely a value of 0, which means that they have not been able to make movements as many as 12 respondents.2.  Most respondents scored FEAS after sensory integration, namely a value of 1 which means that they can make occasional movements and a value of 2 which means that they can consistently perform movements as many as 7 respondents each.3.  There was a sensory effect of integration on gross motor changes in hyperactiv children at the Yamet child development clinic, East Surabaya branch, with a Wilcoxon significance of 0.001<α (α=0.05).